Rethinking coal : chemicals and carbon-based materials in the 21st century - Schobert, Harold H., 1943- (Oxford University Press, 2022)
"The 2016 Nobel Laureate in Literature has eloquently characterized the coal situation today: "The times they are a-changin'." On or about December 2010, the coal industry worldwide seemed to be in great shape. Global demand for coal had not only recovered from the 2008 recession, but was by then expanding at annual rates"-- Provided by publisher.
Keywords: Coal trade -- History -- 21st century.; elektronické knihy; electronic books